A Comparative Study of Query Processing and Optimization Techniques - Thangam, A. Regit; Peter, S.John (International Journal of Computer Sciences and Engineering, 2025)
The importance for optimization arises from the flexibleness provided by modern user interfaces to databases. With the widespread applications of Database Management Systems, users have to deal with an enormous amount of data. Therefore, it is necessary to store this data in such a way that it is retrieved from the information within the quickest possible manner to satisfy the request from a user. Databases are most helpful in representing information in an organized manner. It provides the user with the flexibility to acquire correct, reliable and timely data for effective decision making process. Thus, the importance of database systems is increasing day by day. At the same time, the complexity in queries is also increasing day by day which makes the problem of determining the best query optimization technique. Query optimization in databases continues to be an important issue in various fields for a long period of time. To reduce the execution cost, we need to reformulate the complex query with computationally equivalent and more efficient one. Now in this paper, we analyse and compare the performance of various query processing techniques like Aggregate function based approach, Reduced function based approach, Bitmap Index based approach, Filtered Bitmap Index based approach to process queries with set predicate